The Role of Phonetics in Pronunciation English Borrowing in Medical Terminology - Khamdamova Shakhnoza Yusupalievna (Procedia of Social Sciences and Humanities, 2022)
The purpose of the study is to study the process of borrowing medical terminology, expressions used in the daily speech of a physician, the causes and methods of the emergence of foreign words. The relevance of this study lies in the need to understand the exact meaning of frequently used words and expressions of medical vocabulary, as well as the exact knowledge of their etymology.